What role for cognitive remediation in the treatment of depressive symptoms? A superiority and noninferiority meta‐analysis for clinicians. Issue 7 (10th May 2022) - Sociali, Antonella; Borgi, Marta; Pettorruso, Mauro; Di Carlo, Francesco; Di Natale, Chiara; Tambelli, Antonio; Alessi, Maria C.; Ciavoni, Laura; Mosca, Alessio; Miuli, Andrea; Sensi, Stefano L.; Martinotti, Giovanni; et al.
Abstract: Background: Cognitive remediation (CR) is a promising technique in the treatment of the cognitive dimension of depression. The present study evaluated the potential of CR in treating depressive symptoms and provides practical information about its usefulness in clinical settings. Methods: We performed two meta‐analyses of published randomized (and nonrandomized) clinical trials, comparing CR to control conditions in subjects with current depressive symptomatology. The superiority meta‐analysis aimed to determine the superiority of CR when compared with placebo/waiting list interventions and its efficacy when used as an augmentation therapy. The noninferiority meta‐analysis determined whether CR had noninferior efficacy compared with standard antidepressant interventions. Results: CR was found to significantly improve depressive symptomatology in the superiority meta‐analysis (CR: n = 466, control n = 478). Moreover, CR seemed to be noninferior to standard antidepressant interventions (CR: n = 230, control n = 235). CR was more effective when addressing hot (vs. cold) cognition, when involving younger patients (i.e., <30 years), and in the case of mild‐moderate (vs. severe) depression. Conclusions: CR should be considered an augmentation treatment to improve treatment outcomes in depressed subjects, especially among young individuals. Interventions addressing hot cognition seem to be the most promising.